Aluminium Metal Matrix Composites and their Reinfrocements, The Need of Automotive : A Review - Anuj Asati (Journal of Advanced Research in Mechanical Engineering and Technology, 2025)
Aluminium Metal Matrix Composites (AMMCs) have gained significant attention in recent years due to their potential to revolutionize the automotive industry. This review paper provides a comprehensive analysis of the various aspects of AMMCs, their advancements, reinforcement materials used, the effects of these reinforcements such as [silicon carbide (SiC), alumina (Al2O3), Boron carbide (B4C), Carbon nanotubes, Magnesium Oxide (MgO), TiB2, ZrO2] , and the potential applications of AMMCs in automobile components. The paper explores the intricate interplay between matrix materials, reinforcement types, manufacturing techniques, and their impact on the mechanical and functional properties of AMMCs. Understanding the current state of AMMC research and development is vital to enhance the performance and sustainability of automotive components.